Three-Dimensional Numerical Simulation of Fracture Extension in Conglomerate Fracturing Considering Pore-Fracture Seepage and Study of Influencing Factors - Zehao Xu; Haiyang Zhao; Xiangjun Liu; Lixi Liang; Pandeng Luo (Geofluids)
The nonhomogeneity of conglomerate in terms of organization and the complexity of fracture extension make the design and effective implementation of fracturing in conglomerate reservoirs challenging. Considering the limitations of physical experiments and two-dimensional (2D) numerical modeling, this paper adopts the continuum-discontinue element method (CDEM) to carry out numerical simulation of three-dimensional (3D) conglomerate fracturing considering pore-fracture seepage. By introducing multiple parameters to quantify the correlation between fracture geometry, fracture complexity, and damage mode, the evolution mechanism of fracture morphology under the influence of multiple factors is systematically investigated. The results show that the numerical simulation experiments can control the variables well, but the random distribution of gravel leads to the unpredictability of fracture extension, and the concluding patterns obtained still show large fluctuations. The high permeability of the gravel promotes the development of gravel-penetrating fractures but has less effect on the overall morphology of the fractures. High-strength gravel promotes the development of branching fractures in the initiation phase, which acts as a barrier to expanding fractures, and the most complex fracture development occurs when the gravel strength is approximately 4–5 times that of the matrix. In the weakly cemented state, fracture development around the gravel contributes to the shear failure of the conglomerate, but the strength of the cemented interface has no obvious control on the overall fracture morphology. The correlation between gravel content and conglomerate damage mode is significant, with the highest degree of fracture complexity occurring when the gravel content is approximately 30%. Stress differential is the most significant controlling factor affecting fracture morphology, followed by minimum principal stress. When the stress difference reaches 8 MPa, the fracture morphology begins to stabilize, and too high a stress difference will cause the phenomenon that the fracture stops expanding, affecting the fracturing effect. A high level of minimum stress promotes tensile failure in conglomerate, and the scale and complexity of fracture decrease. High injection displacement promotes branch fracture development and reduces the effect of in situ stress on fracture extension, and too high a displacement leads to inhibition of main fracture development.